2021
DOI: 10.1177/03000605211063105
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in patients with colorectal cancer after colostomy: a longitudinal study in Shanghai

Abstract: Objective Research is lacking regarding the experiences of patients after colostomy, which is needed so as to take necessary specific actions. In this study, we aimed to describe the trajectory of symptom clusters experienced by patients after colostomy over time. Methods This was a longitudinal observational study using data from 149 patients with colorectal cancer after colostomy. We investigated symptoms and symptom clusters at 2 weeks, 1 month, 3 months, 6 months, and 1 year after colostomy. Results Four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Due to the nature of these symptoms, patients can have accompanying embarrassment in social settings. The gastrointestinal symptoms cluster, often characterized as “digestive symptoms cluster”, is frequently identified in the previous literature in CRC patients [ 13 , 36 ] and patients with other cancer types [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nature of these symptoms, patients can have accompanying embarrassment in social settings. The gastrointestinal symptoms cluster, often characterized as “digestive symptoms cluster”, is frequently identified in the previous literature in CRC patients [ 13 , 36 ] and patients with other cancer types [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that multiple symptoms cluster together in CRC survivors, suggesting that these symptoms may be interconnected and share underlying mechanisms [ 12 ]. For example, one study identified four distinctive symptom clusters (psychological, digestive and urinary, low energy, and pain) in CRC patients during the first year after surgery [ 13 ]. Functional status and quality of life are often significantly impaired among CRC survivors who experience these adverse symptoms simultaneously [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency, percentage, mean, and standard deviation were used to describe the demographic data and symptom occurrence of patients. In the process of data analysis, we excluded uncommon symptoms (prevalence < 10%) [ 31 33 ], including decreased interest in sex and difficulty becoming sexually aroused, from the analysis in order not to bias the results. Therefore, we actually included 28 symptoms in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…JASP version 0.15 (JASP Team) [17] was used for network analysis. Symptoms were the nodes in the network, and edges represent the independent relationship between two nodes in the network.…”
Section: Symptom Network and Node Centralitymentioning
confidence: 99%